Surgery in Neonatal and Pediatric ECMO Patients Other Than Congenital Diaphragmatic Hernia Repair: A 10-Year Experience - Kersten, Casper M.; Hermelijn, Sergei M.; Wijnen, René M. H.; Tibboel, Dick; Houmes, Robert J. M.; Schnater, J. Marco (Frontiers in Pediatrics, 2021)
Aim of study: The use of extracorporeal membrane oxygenation (ECMO) has increased as a result of technological developments and the expansion of indications. Relatedly, the number of patients undergoing surgery during ECMO is also rising, at least in the adult population. Little is known on surgery in children during ECMO-therapy. We therefore aimed to assess the frequencies and types of surgical interventions in neonatal and pediatric patients on ECMO and to analyze surgery-related morbidity and mortality. Methods: We retrospectively collected information of all patients on ECMO over a 10-year period in a single tertiary and designated ECMO-center, excluding patients undergoing cardiac surgery and correction of congenital diaphragmatic hernia. Chi-squared test and Mann-Whitney U test were used to analyze data. Main results: Thirty-two of 221 patients (14%) required surgery when on ECMO. Common interventions were thoracotomy (32%), laparotomy (23%), fasciotomy (17%) and surgical revision of ECMO (15%). Complications occurred in 28 cases (88%), resulting in a 50% in-hospital mortality rate. Surgical patients had a longer ICU stay and longer total hospital stay compared to those not receiving surgery during ECMO. No significant difference in mortality was found when comparing surgical to non-surgical patients (50% versus 41%). Conclusions: Approximately one in seven neonatal or pediatric patients required surgical intervention during ECMO, of whom almost 90% developed a complication, resulting in a 50% mortality rate. These results should be taken into account in counseling.